The Transcription Factor NFATc1 Supports the Rejection of Heterotopic Heart Allografts - Baur, Johannes; Otto, Christoph; Steger, Ulrich; Klein-Hessling, Stefan; Muhammad, Khalid; Pusch, Tobias; Murti, Krisna; Wismer, Rhoda; Germer, Christoph-Thomas; Klein, Ingo; Müller, Nora; Serfling, Edgar; et al. (Frontiers in Immunology, 2018)
The immune suppressants cyclosporin A (CsA) and tacrolimus (FK506) are used worldwide in transplantation medicine to suppress graft rejection. Both CsA and FK506 inhibit the phosphatase calcineurin (CN) whose activity controls the immune receptor-mediated activation of lymphocytes. Downstream targets of CN in lymphocytes are the Nuclear Factors of Activated T Cells (NFATs). We show here that the activity of NFATc1, the most prominent NFAT factor in activated lymphocytes supports the acute rejection of heterotopic heart allografts. While ablation of NFATc1 in T cells prevented graft rejection, ectopic expression of inducible NFATc1/aA isoform led to rejection of heart allografts in recipient mice. Acceptance of transplanted hearts in mice bearing NFATc1-deficient T cells was accompanied by a reduction in number and cytotoxicity of graft infiltration cells (GICs). In CD8+T cells, NFATc1 controls numerous intracellular signaling pathways that lead to the metabolic switch to aerobic glycolysis and the expression of numerous lymphokines, chemokines and their receptors, including Cxcr3 that supports the rejection of allogeneic heart transplants. These findings favors NFATc1 as a molecular target for the development of new strategies to control the cytotoxicity of T cells upon organ transplantation.